2016
DOI: 10.1186/s12879-016-1484-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of febrile urinary tract infection among spinal cord injured patients

Abstract: BackgroundUrinary tract infection (UTI) among patients with neurogenic bladder is a major problem but its management is not well known. We studied the relationship between antibiotic regimen use and the cure rate of those infections among 112 patients with neurogenic bladder.MethodsWe studied a retrospective cohort of febrile UTI among patients with neurogenic bladder. Drug selection was left to the discretion of the treating physicians, in accordance with current guidelines. Patients were divided into 3 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…In older adults, who are particularly susceptible to antibiotic-related adverse events, the risk-benefit calculus of antibiotic treatment favors shorter lengths of therapy. Mounting evidence demonstrates that clinical cure can be effective achieved for CAUTI using a short course of antibiotics (≤7 days) when the catheter is removed if the patient is responding rapidly to initial therapy [8082]. Similarly, longer lengths of therapy (>7 days) do not prevent recurrent UTIs and instead are associated with increased C. difficile infection [18].…”
Section: Treatment Of Utismentioning
confidence: 99%
“…In older adults, who are particularly susceptible to antibiotic-related adverse events, the risk-benefit calculus of antibiotic treatment favors shorter lengths of therapy. Mounting evidence demonstrates that clinical cure can be effective achieved for CAUTI using a short course of antibiotics (≤7 days) when the catheter is removed if the patient is responding rapidly to initial therapy [8082]. Similarly, longer lengths of therapy (>7 days) do not prevent recurrent UTIs and instead are associated with increased C. difficile infection [18].…”
Section: Treatment Of Utismentioning
confidence: 99%
“…Longer durations of therapy are required for more severe (febrile) UTIs that indicate involvement of the upper urinary tract, or in patients with a delayed response. 8,9,15 There was no difference in the recurrence rate of UTI between patients in the acute and chronic phases of SCI, either at W3 (4/14 vs 7/56) or at W6 (5/13 vs 18/48). Thus, there is no rationale for a longer duration of treatment in the acute phase.…”
Section: Treatment Durationmentioning
confidence: 91%
“…In a recent retrospective study of 112 patients, Dinh et al 15 found no difference in cure rates for febrile UTI treated with o10 days, between 10 and 15 days, and more than 15 days of ATBs. The results suggested that a treatment duration of 8 days was appropriate in the case of febrile UTI.…”
Section: Treatment Durationmentioning
confidence: 97%
“…Usually, even in patients with febrile UTI, a monotherapy is sufficient. There is no difference in the cure rate comparing treatment with a single substance versus dual therapy 15. In hospitalized patients with severe infection suspicious for methicillin-resistant Staphylococcus aureus (MRSA), vancomycin is an option.…”
Section: Uti Treatmentmentioning
confidence: 99%